Endothelial cell-derived small extracellular vesicles suppress cutaneous wound healing through regulating fibroblasts autophagy. (2nd May 2019) - Zeng, Tingting; Wang, Xiaoyi; Wang, Wei; Feng, Qiling; Lao, Guojuan; Liang, Ying; Wang, Chuan; Zhou, Jing; Chen, Yuying; Liu, Jing; Gao, Haiqi; Lan, Biyun; et al.
Abstract : Diabetic foot ulcer is a life-threatening clinical problem in diabetic patients. Endothelial cell-derived small extracellular vesicles (sEVs) are important mediators of intercellular communication in the pathogenesis of several diseases. However, the exact mechanisms of wound healing mediated by endothelial cell-derived sEVs remain unclear. sEVs were isolated from human umbilical vein endothelial cells (HUVECs) pretreated with or without advanced glycation end products (AGEs). The roles of HUVEC-derived sEVs on the biological characteristics of skin fibroblasts were investigated both in vitro and in vivo . We demonstrate that sEVs derived from AGEs-pretreated HUVECs (AGEs-sEVs) could inhibit collagen synthesis by activating autophagy of human skin fibroblasts. Additionally, treatment with AGEs-sEVs could delay the wound healing process in Sprague–Dawley (SD) rats. Further analysis indicated that miR-106b-5p was up-regulated in AGEs-sEVs and importantly, in exudate-derived sEVs from patients with diabetic foot ulcer. Consequently, sEV-mediated uptake of miR-106b-5p in recipient fibroblasts reduces expression of extracellular signal-regulated kinase 1/2 (ERK1/2), resulting in fibroblasts autophagy activation and subsequent collagen degradation. Collectively, our data demonstrate that miR-106b-5p could be enriched in AGEs-sEVs, then decreases collagen synthesis and delays cutaneous wound healing by triggering fibroblasts autophagy through reducing ERK1/2 expression.